Kinetic Analysis of Substrate Utilization by Native and TNAP-, NPP1-, or PHOSPHO1-Deficient Matrix Vesicles - Ciancaglini, Pietro; Yadav, Manisha C.; Sper Simao, Ana Maria; Narisawa, Sonoko; Pizauro, Joao Martins [UNESP]; Farquharson, Colin; Hoylaerts, Marc F.; Millan, Jose Luis (John Wiley & Sons Inc, 2010)
During the process of endochondral bone formation, chondrocytes and osteoblasts mineralize their extracellular matrix by promoting the formation of hydroxyapatite seed crystals in the sheltered interior of membrane-limited matrix vesicles (MVs) Here, we have studied phosphosubstrate catalysis by osteoblast-derived MVs at physiologic pH, analyzing the hydrolysis of ATP, ADP, and PP, by isolated wild-type (WT) as well as TNAP-, NPP1- and PHOSPHO1-deficient MVs Comparison of the catalytic efficiencies identified ATP as the main substrate hydrolyzed by WT MVs The lack of TNAP had the most pronounced effect on the hydrolysis of all physiologic substrates The lack of PHOSPHO1 affected ATP hydrolysis via a secondary reduction in the levels of TNAP in PHOSPHO1-deficient MVs. The lack of NPP1 did not significantly affect the kinetic parameters of hydrolysis when compared with WT MVs for any of the substrates We conclude that TNAP is the enzyme that hydrolyzes both ATP and PP, in the MV compartment NPP1 does not have a major role in PP, generation from ATP at the level of MVs, in contrast to its accepted role on the surface of the osteoblasts and chondrocytes, but rather acts as a phosphatase in the absence of TNAP (C) 2010 American Society for Bone and Mineral Research
Keywords: BIOMINERALIZATION; KNOCKOUT MICE; Calcification; PYROPHOSPHATASES; ATPASES